Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.15252/embj.2019104238
|View full text |Cite
|
Sign up to set email alerts
|

Phytohormone cytokinin guides microtubule dynamics during cell progression from proliferative to differentiated stage

Abstract: Cell production and differentiation for the acquisition of specific functions are key features of living systems. The dynamic network of cellular microtubules provides the necessary platform to accommodate processes associated with the transition of cells through the individual phases of cytogenesis. Here, we show that the plant hormone cytokinin fine‐tunes the activity of the microtubular cytoskeleton during cell differentiation and counteracts microtubular rearrangements driven by the hormone auxin. The endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 110 publications
1
18
0
Order By: Relevance
“…[ 45 , 46 ]. Recently, it was demonstrated that cytokinins control the rearrangement of cortical microtubules from transverse orientation in the transition and elongation zones to oblique orientation in the differentiation zone in the epidermal cells of A. thaliana root [ 47 ]. Intriguingly, the localization of auxin in the symbiotic nodules of L. japonicus [ 48 ] and P. sativum [ 49 ] is limited to the meristem and vascular tissues.…”
Section: Discussionmentioning
confidence: 99%
“…[ 45 , 46 ]. Recently, it was demonstrated that cytokinins control the rearrangement of cortical microtubules from transverse orientation in the transition and elongation zones to oblique orientation in the differentiation zone in the epidermal cells of A. thaliana root [ 47 ]. Intriguingly, the localization of auxin in the symbiotic nodules of L. japonicus [ 48 ] and P. sativum [ 49 ] is limited to the meristem and vascular tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the root cell elongation is also inhibited using a high IAA concentration (250nm) or in the OE of YUC6 compared to control conditions, probably by a transitory alkalinization of the apoplast ( Barbez et al, 2017 ; Figure 4B ). Moreover, cells in the EZ have transversal microtubules that are more sensitive to auxin−driven reorientation of the microtubule network to longitudinal disposition than in other PR zones leading to a reduced cellular elongation rate ( Montesinos et al, 2020 ). Additionally, many different PIN mutants have a reduction in the cell elongation size compared to WT and high levels of PLT2 expression or PLT2 protein in the EZ inhibit cell elongation ( Galinha et al, 2007 ; Mähönen et al, 2014 ) ( Blilou et al, 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, ethylene has inhibitory effects in dark conditions, and its action is canceled after the hypocotyl emerges from the soil and becomes exposed to ambient light ( Yu and Huang, 2017 ). Meanwhile, auxin promotes hypocotyl elongation in light conditions, but has rudimentary effects in the dark ( Jensen et al, 1998 ), while cytokinins establish an acropetal root gradient underlying the developmental zonation of the root ( Montesinos et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%